2001
DOI: 10.1006/viro.2000.0835
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Protein Expression Induces Apoptosis in HepG2 Cells

Abstract: The mechanisms of hepatocyte death and the events that lead to a high rate of chronic liver disease in patients infected with hepatitis C virus are not known. We established a HCV replication system in HepG2 cell culture and utilized this model to address the effect of HCV proteins on HepG2 cell growth and viability. After transfection of HepG2 cells with full-length RNA, a truncated RNA, or an antisense RNA, cell proliferation and cell viability were analyzed by thymidine uptake and the trypan blue exclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 29 publications
1
18
0
2
Order By: Relevance
“…Additionally, some cells exhibited discrete hyperplastic modifications of ER cisternae or altered mitochondria of abnormal, irregular shape which were sometimes vacuolized or with thinned and fragmented cristae similar to those observed by others (not shown) (2). Particular morphological alterations of nuclei potentially caused by apoptosis as described by others for HepG2 cell transfected with full-length HCV RNA (37) could not be detected.…”
Section: Establishment Of Huh-7 Cells Carrying Sfl Genomessupporting
confidence: 77%
“…Additionally, some cells exhibited discrete hyperplastic modifications of ER cisternae or altered mitochondria of abnormal, irregular shape which were sometimes vacuolized or with thinned and fragmented cristae similar to those observed by others (not shown) (2). Particular morphological alterations of nuclei potentially caused by apoptosis as described by others for HepG2 cell transfected with full-length HCV RNA (37) could not be detected.…”
Section: Establishment Of Huh-7 Cells Carrying Sfl Genomessupporting
confidence: 77%
“…Overexpression of HCV glycoproteins activates grp78 and grp94 promoters in transient gene expression assays, consistent with the induction of an ER stress response (24). In addition, expression of HCV proteins in a hepatoma cell line (HepG2) induces apoptosis (21). Therefore, it is tempting to speculate that BVDV-induced ER stress is mediated through signals that emanate from the ER lumen and are caused by the presence of unfolded or unassembled viral glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that core protein modulates the death receptor pathway of apoptosis, the activation of other apoptosis pathways by HCV proteins has not been analyzed. Interestingly, it has been reported that expression of the complete structural region or the full-length genome may directly induce cytotoxicity in osteosarcoma [25] and hepatoma cell lines [17].…”
mentioning
confidence: 99%